Cavitating flow structures and corresponding hydrodynamics of a transient pitching hydrofoil in different cavitation regimes. (November 2020) - Mengjie, Zhang; Biao, Huang; Zhongdong, Qian; Taotao, Liu; Qin, Wu; Hanzhe, Zhang; Guoyu, Wang
Highlights: Analyze the influence of cavitation on the hydrodynamic load coefficients and surrounding flow structures. Explain the interdependency between the cavity and vorticity dynamics. Investigate the evolution of cavitating flow structure around the pitching hydrofoil for sheet cavitation and cloud cavitation regimes. Abstract: The present paper applied experimental and numerical methods to investigate the cavitating flow structures and corresponding hydrodynamics for a transient pitching Clark-Y hydrofoil. The aims are to (1) improve the understanding of the interplay between the transient cavitating flow structures, motion of the hydrofoil, and hydrodynamic performance, (2) quantify the influence of cavitation on the hydrodynamic load coefficients and flow structures, and (3) analyze the evolution of cavitating flow during different cavitation regime. The pitching motion trajectory is a triangular wave with mean incidence of α0 =10° and amplitude of Δα = 5° at a frequency of 2 Hz. The upstream velocity U ∞ is fixed at 6.3 m/s, which is corresponding to Re =4.4 × 10 5 . The cavitation patterns for different cavitation numbers are mainly documented by the high-speed photography, and the dynamic characteristics of the hydrofoil are measured by the torque sensor. The numerical investigations were performed by solving the incompressible URANS equations using the mass-transfer cavitation model, the coupled k-ω SST turbulence model and γ - Re θ transition model. The predicted cavity patterns and moment coefficients agree well with the experimental results. Four typical regimes, including sub cavitation, inception cavitation, sheet cavitation and cloud cavitation, are observed. Compared to the sub cavitation case, the hydrodynamic coefficients and flow structures are significantly affected by the incipient cavity. Results show that the leading edge (LE) cavity promotes the formation of the counterclockwise tailing edge vortex (TEV), thus leading to decline of the lift. Moreover, the LE cavity also limits the formation of the clockwise second vortex (SV), which weakens the fluctuation of the hydrodynamic load. For the sheet cavitation case, three cavitating flow patterns(Pattern A/B/C) are observed in the hydrodynamic fluctuation stage, which is corresponding to different characteristic frequency. For the cloud cavitation case, the hydrodynamic curves present four distinct stages. According to the cavity breaking position and characteristic frequency, four different patterns(Pattern I/II/III/IV) of the cavity development and shedding are observed and analyzed.